Long-term application of Swedish sewage sludge on farmland does not cause clear changes in the soil bacterial resistome. (April 2020) - Rutgersson, Carolin; Ebmeyer, Stefan; Lassen, Simon Bo; Karkman, Antti; Fick, Jerker; Kristiansson, Erik; Brandt, Kristian K.; Flach, Carl-Fredrik; Larsson, D.G. Joakim
Highlights: Application of sewage sludge did not cause accumulation of antibiotics in soil. There was no detected increase in phenotypic resistance after sludge application. Long-term sludge-amendment did not cause enrichment of resistance genes in soil. Sludge application had very subtle effects on microbial community composition. Bioavailable Cu was higher in long-term sludge-amended soil than in controls. Abstract: The widespread practice of applying sewage sludge to arable land makes use of nutrients indispensable for crops and reduces the need for inorganic fertilizer, however this application also provides a potential route for human exposure to chemical contaminants and microbial pathogens in the sludge. A recent concern is that such practice could promote environmental selection and dissemination of antibiotic resistant bacteria or resistance genes. Understanding the risks of sludge amendment in relation to antibiotic resistance development is important for sustainable agriculture, waste treatment and infectious disease management. To assess such risks, we took advantage of an agricultural field trial in southern Sweden, where land used for growing different crops has been amended with sludge every four years since 1981. We sampled raw, semi-digested and digested and stored sludge together with soils from the experimental plots before and two weeks after the most recent amendment in 2017. Levels of selected antimicrobials and bioavailable metals were determined and microbial effects were evaluated using both culture-independent metagenome sequencing and conventional culturing. Antimicrobials or bioavailable metals (Cu and Zn) did not accumulate to levels of concern for environmental selection of antibiotic resistance, and no coherent signs, neither on short or long time scales, of enrichment of antibiotic-resistant bacteria or resistance genes were found in soils amended with digested and stored sewage sludge in doses up to 12 metric tons per hectare. Likewise, only very few and slight differences in microbial community composition were observed after sludge amendment. Taken together, the current study does not indicate risks of sludge amendment related to antibiotic resistance development under the given conditions. Extrapolations should however be done with care as sludge quality and application practices vary between regions. Hence, the antibiotic concentrations and resistance load of the sludge are likely to be higher in regions with larger antibiotic consumption and resistance burden than Sweden.